Peran Olahraga Sebagai Strategi Peningkatan Komunikasi dan Elektabilitas Politik Anggota Dewan Perwakilan Rakyat Kota Banda Aceh - Irfandi Fandi; Zikrur Rahmat (Yayasan Hurriah, Banda Aceh, 2021)
English: This research study aims to determine the Pattern of Achievement Development of Taekwondo Athletes at the Aceh Sports Talent High School (SMAKOR) regarding the knowledge and personal trainers who handle athletes towards high achievement, the condition of athletes which includes physical, talent and motivation in branch athletes. Taekwondo sports at the Aceh Sports Talent High School (SMAKOR), a supporting facility for improving the achievements of athletes in the Taekwondo sport at the Aceh Sports Talent High School (SMAKOR) the role of School/Education for athletes with achievements in sports. which includes this study using a descriptive qualitative approach with the Countenance evaluation model from Robert E. Stake. The subjects of this study were administrators, coaches and athletes in Taekwondo at the Aceh Sports Talent High School (SMAKOR). Data collection techniques in this study were observation, interviews and documentation. The data analysis technique used is data triangulation, namely by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study are: The antecedents, background and planning of the coaching program in Taekwondo at the Aceh Sports Talent High School (SMAKOR) are clear and well organized. Transactions, recruitment of coaches and athletes have gone well, the implementation of the coaching program is good enough according to the scheduled training program, the facilities and infrastructure are not good and some are not standardized nationally, the funds have not run well enough to meet the needs of athletes, consumption has not gone well enough to meet the needs of athletes. meet the needs of athletes, coordination has gone well, the welfare provided to coaches and athletes has not been maximized. The outcome is that the athletes' achievements in several sports have been good but not stable and some have not even received significant achievements. Conclusion: The antecedents, background and planning of the coaching program are good and clear. Transactions, recruitment of coaches and athletes have gone well, the implementation of the coaching program is quite good, facilities and infrastructure are not good, funds are not good, consumption is not good, and the welfare provided to coaches and athletes is not optimal. Outcome, the achievements of Taekwondo athletes at the Aceh Sports Talent High School (SMAKOR) in several sports have been good but not stable and some have not even received significant achievements. Bahasa: Penelitian ini dilatar belakangi oleh peran dan konstribusi anggota dewan dalam meningkatkan elektabilitasnya dimata masyarakat terutama bidang olahraga dimana, masyarakat sangat meninginkan adanya penyelenggaraan event olahraga pada setiap tahunnya oleh para anggota dewan, sebab yang menjadi pokok permasalahan selama ini kebanyakan anggota dewan tidak pernah merespon, mempedulikan para pendukungnya semasa pemilihan umum, pemilihan anggota dewan. Tujuan penelitian yakni untuk meningkatkan elektabilitas para anggota dewan dan strategi peningkatan komunikasi dan elektabilitas politik Anggota Dewan Perwakilan Rakyat Kota Banda Aceh. Metode yang digunakan pendekatan kualitatif, pemilihan pendekatan kualitatif dengan menggunakan metode survey dikarenakan dalam melakukan tindakan ditujukan kepada subyek penelitian, peneliti mengutamakan dan mengungkapkan makna dalam proses kegiatan penelitian. Hasil penelitian para anggota dewan harus senantiasa memperhatikan dan memberi perhatian lebih kepada para anak muda, pemerhati olahraga dan masyarakat dimana mereka memang sudah layak dan seyogyanya mendapatkan kesempatan lebih dalam penyelenggaraanevent pada cabang olahraga tertentu, sebab dengan adanya penyelenaggaraan event padaberbagai ajang dan cabang olahraga tertentu maka dengan sendirinya akan meningkatkanelektabilitas dan pamor anggota dewan itu sendiri. Dengan mendukung sejumlah eventperlombaan dalam penyelenggaraan berbagai aktivitas tersebut maka Anggota DPRK BandaAceh ini akan lebih terpandang, dipercaya oleh sejumlah kalangan masyarakat sehingga harapannya kedepan akan lebih mudah untuk menduduki posisi yang sama atau pun naikjabatannya sebagai wakil rakyat.